Characteristics of Electrical Power Generation by Wind for Al-Tweitha Location Using Weibull Distribution Function - A. Abdulwahab, Rawnak; H. Shaban, Auday; H Nasser, Eshtar (Iraqi Journal of Science, 2023)
In this paper, the 5 minutes measured wind speed data for year 2012 at 10 meter height for Tweitha have been statically analyzed to assess the time of wind turbine electrical power generation. After collection Tweitha wind data and calculation of mean wind speed the cumulative Weibull diagram and probability density function was ploted, then each of cumulative Weibull distribution, cut-in and furling turbine wind speed could be used as a mathematical input parameters in order to estimate the hours of electrical power generation for wind turbine during one day or one year. In Tweitha site, found that the average wind speed was (v= 1.76 m/s), so five different wind turbines were be selected to calculate hours of electrical generation for Al-Tweitha site, the best of them was SWG 20 kW wind turbine.